Cereal Grains Volume 1 - Kumar Goyal, Aakash (IntechOpen, 2021)
Over the past 50 years, cereals such as maize, rice, wheat, sorghum, and barley have emerged as rapidly evolving crops because of new technologies and advances in agronomy, breeding, biotechnology, genetics, and so on. Population growth and climate change have led to new challenges, among which are feeding the growing global population and mitigating adverse effects on the environment. One way to deal with these issues is through sustainable cereal production. This book discusses ways to achieve sustainable production of cereals via agronomy, breeding, transcriptomics, proteomics, and metabolomics. Chapters review research, examine challenges, and present prospects in the field. This volume is an excellent resource for students, researchers, and scientists interested in and working in the area of sustainable crop production.